Kebijakan kawasan tanpa rokok hubungannya dengan status merokok pada laki-laki di Indonesia: analisis lanjut survei indikator kesehatan Indonesia (Sirkesnas) 2016 - Nur Aeni Amaliah (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Smoke-free area policy and smoking status in men in Indonesia: further analysis of the 2016 Indonesia health indicators survey (Sirkesnas)Purpose: This study was conducted to analyze the Smoke-Free Area (SFA) policy, whether there is a relationship between smoking room restrictions and the smoking status of men in Indonesia. Method: A cross-sectional study design using 2016 National Health Indicator Survey (Sirkesnas) was used to assess the relationship between SFA policy, marital status, age, education level, type of work and residence (rural/urban) and smoking status of male population in Indonesia is ≥10 years old. The analysis uses quadratic analysis to assess the relationship between smoking status and non-smoking area policy, and logistic regression analysis to find out the variables that together influence the smoking status of men in Indonesia. This study did not analyze the implementation of policies in the district/city. Results: There is a relationship between SFA policy (OR: 1.11; 95% CI: 1.06-1.16), marital status (OR: 5.21; 95% CI: 4.95-5.49), age (OR: 11.80; 95% CI 11.02-12.63), education level (OR: 1.96; 95% CI: 1.79-2.15), type of work (OR: 8.94; 95% CI: 8.39-9.53), and residence (OR: 1.14; 95% CI: 1.09-1.20) with smoking status in men in Indonesia. The variables which mostly influence men's smoking status in Indonesia were SFA policy, marital status, age, education level, and type of work. Conclusion: SFA policies in districts/cities in Indonesia were related to smoking status in men in Indonesia. All regencies/cities must have an SFA policy and implement it, as a comprehensive tobacco control effort in Indonesia. The implementation of SFA policies in districts/cities needs to be increased so that the effects of suppressing smoking prevalence can be seen.